PENGUATAN JIWA KEWIRAUSAHAAN MELALUI PELATIHAN INOVASI PRODUK LOKAL BAGI SISWA SMK YADIKA NATAR - Lusia Septia Eka Esti Rahayu; Marliasari; Rahmi Eliyana; M. Junaidi; Anisah Martiah (LPPI UMN AL WASHLIYAH, 2025)
This community service activity aims to foster and strengthen the entrepreneurial spirit of SMK YADIKA Natar students through training in local product innovation based on the potential of local resources. As future young entrepreneurs, SMK students need to have the ability to innovate in order to develop creative products that are economically valuable and highly competitive. This activity was motivated by the low interest of students in entrepreneurship and their limited understanding of how to turn local potential into promising business opportunities. The training was conducted through an intensive two-day programme with a participatory approach, which included the delivery of basic entrepreneurship material, the development of product ideas based on local potential, product innovation practices, and simple marketing simulations. Each training session was designed to foster active participant involvement, strengthen group collaboration, and instil values of creativity and independence. The activity was evaluated through pre-tests and post-tests to measure the increase in students' knowledge and changes in their entrepreneurial attitudes. The results showed a significant improvement in the students' understanding of entrepreneurial concepts, their ability to innovate, and their confidence in designing new business ideas. In addition, the students also showed high enthusiasm and awareness of the importance of creativity as the main capital in entrepreneurship. This training is expected to be a step forward in developing the entrepreneurial spirit among students.